Atomic‐Scale Studies of Fe(3)O(4)(001) and TiO(2)(110) Surfaces Following Immersion in CO(2)‐Acidified Water - Mirabella, Francesca (Chemphyschem, 2020)
Difficulties associated with the integration of liquids into a UHV environment make surface‐science style studies of mineral dissolution particularly challenging. Recently, we developed a novel experimental setup for the UHV‐compatible dosing of ultrapure liquid water and studied its interaction with TiO(2) and Fe(3)O(4) surfaces. Herein, we describe a simple approach to vary the pH through the partial pressure of CO(2) ([Formula: see text] ) in the surrounding vacuum chamber and use this to study how these surfaces react to an acidic solution. The TiO(2)(110) surface is unaffected by the acidic solution, except for a small amount of carbonaceous contamination. The Fe(3)O(4)(001)‐([Formula: see text] × [Formula: see text] )R45° surface begins to dissolve at a pH 4.0–3.9 ([Formula: see text] =0.8–1 bar) and, although it is significantly roughened, the atomic‐scale structure of the Fe(3)O(4)(001) surface layer remains visible in scanning tunneling microscopy (STM) images. X‐ray photoelectron spectroscopy (XPS) reveals that the surface is chemically reduced and contains a significant accumulation of bicarbonate (HCO(3) (−)) species. These observations are consistent with Fe(II) being extracted by bicarbonate ions, leading to dissolved iron bicarbonate complexes (Fe(HCO(3))(2)), which precipitate onto the surface when the water evaporates.